1999
DOI: 10.1093/jac/43.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial activity of cerulenin and its effects on lipid biosynthesis

Abstract: Cerulenin is a potent inhibitor of fatty acid synthase (FAS) in a variety of prokaryotic and eukaryotic cells. Using a standardized mycobacterial susceptibility test, we have observed that cerulenin inhibits the growth of several species of mycobacteria, including tuberculous species such as Mycobacterium tuberculosis (H37Rv and clinical isolates) and Mycobacterium bovis BCG (hereafter called BCG), as well as several non-tuberculous species: Mycobacterium smegmatis, the Mycobacterium avium-intracellulare compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 19 publications
3
35
0
1
Order By: Relevance
“…Taken together, these results show that M. tuberculosis is more susceptible to 5-Cl-PZA than M. smegmatis. Furthermore, the MICs of cerulenin, a FASI (and possibly FASII) inhibitor (22), and isoniazid, a FASII inhibitor (1,29,30) Table 2 and Fig. 2.…”
Section: Construction Of MCmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results show that M. tuberculosis is more susceptible to 5-Cl-PZA than M. smegmatis. Furthermore, the MICs of cerulenin, a FASI (and possibly FASII) inhibitor (22), and isoniazid, a FASII inhibitor (1,29,30) Table 2 and Fig. 2.…”
Section: Construction Of MCmentioning
confidence: 99%
“…The FASII enoyl-ACP reductase was identified as the target of isoniazid and ethionamide, which are first-and second-line tuberculosis drugs (1), as well as a universal bacterial target for triclosan, a consumer antimicrobial agent (13,(18)(19)(20)(21)28). The fungal metabolites cerulenin and thiolactomycin target the condensing enzymes of the bacterial FASII pathway (10,17,22,24,25). Two studies have shown that 5-chloro-pyrazinamide (5-Cl-PZA) (5, 32) and pyrazinamide (PZA) (32) inhibit M. tuberculosis FASI, indicating that FASI is also a drug target.…”
mentioning
confidence: 99%
“…The combination of vancomycin and cerulenin, a potent long-chain lipid synthesis inhibitor (23,24), was used at a sub-MIC on M. tuberculosis H37Rv and on MDR and XDR M. tuberculosis clinical isolates. Thirteen clinically unrelated isolates were selected from a M. tuberculosis collection (Tuberculosis Center, Public Health Research Institute [PHRI], NJ) (25).…”
mentioning
confidence: 99%
“…In the past, characterization of FAS has been aided through the use of two natural product inhibitors of FAS components, cerulenin and thiolactomycin (15,16,36,(39)(40)(41)(42)46). Cerulenin is a potent inhibitor of both FAS I and FAS II systems while thiolactomycin inhibits only synthases of the FAS II variety.…”
mentioning
confidence: 99%
“…Cerulenin is a potent inhibitor of both FAS I and FAS II systems while thiolactomycin inhibits only synthases of the FAS II variety. Activity of both of these inhibitors on the mycolic acids of mycobacteria has recently been described (25,42,50). Although cerulenin and thiolactomycin are structurally different, both compounds inhibit the two-carbon homologation catalyzed by the ␤-ketoacyl synthase, the condensing enzyme required for fatty acid biosynthesis.…”
mentioning
confidence: 99%